Legal Principles Under Criminal Law in Indonesia Dan Thailand - Anirut Chuasanga; Ong Argo Victoria (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The principle of legality is known in modern criminal law emerge from the scope of sociological Enlightenment doctrine that exalts the protection of people from abuse of power. Before coming Age of Enlightenment, the power to punish even without any regulations first. At that time, tastes kekuasaanlah most right to determine whether an act to be punished or not. To combat that, exists the principle of legality which is an important instrument of the protection of individual liberties in the face of the country. Thus, what is called the action that can be put into a regulatory authority, not power. According to legal experts, the roots of the idea of the principle of legality is derived from the provisions of Article 39 of the Magna Carta (1215) in the United Kingdom which ensure the protection of people from arrest, detention, seizure, disposal, and release of a person from the protection of the law / legislation, unless there is a judicial decision legitimate. This provision is followed Habeas Corpus Act (1679) in the UK that requires someone who is arrested is checked in a short time. This idea inspired the emergence of one of the provisions in the Declaration of Independence (1776) in the United States that says, no one should be prosecuted or arrested in addition to, and because of the actions set out in, legislation.Keywords: Principle of Legality; Criminal law; Indonesia; Thailand.